Kemampuan Bernalar Secara Analogi dalam Wacana Oleh Siswa : Studi Kasus SMK Swasta Parulian-3 Medan - Deminar Nababan (Cendikia : Media Jurnal Ilmiah Pendidikan, 2020)
This study examines the ability to reason analogously in the discourse of students of Parulian-3 Medan Private Vocational School. The population of this study is all students of Parulian-3 Medan Private Vocational School as many as 182 people. A study sample of 28 people who were randomly taken in class I. The instruments used as many as 10 brief discourses, each short discourse has one conclusion. If one conclusion then the weight is 10, so the total value is 100. The formula used to analyze the data is the percentage of univariate statistics. The method in this study is descriptive method. The results of the study obtained the highest score of 90 and the lowest score of 70, the average score of 82.21, mode of 79 and the median of 79. To find the ability to reason analogously students of Private Vocational School Parulian-3 Medan used the formula to look for averages. From the formula obtained the results of the ability to reason analogously students of Private Vocational School Parulian-3 Medan is 82,21is ongood criteria.